Sheikh Al-Nawdhi's stance on matters of faith based on hearsay from a doctrinal perspective: An inductive and analytical study - Ibrahim, Prof. Dr. Nouri Abdulrahman; Hassan, Asst.Prof.Dr. Ramziya Hamza (Sulaimani Journal for Humanities, 2024)
The Kurds are no less important than other nations, and indeed they have surpassed them in many fields of science, knowledge, and creativity. Many innovators have emerged from among them in several fields, in which they were pioneers, and others followed them in these fields, drawing from the wellsprings of their knowledge and learning. This study deals with an aspect of a Kurdish personality who had a distinctive mark in scientific, religious, and literary circles, and whose high standing in this regard has led to his fame exceeding the borders of Kurdistan to neighboring countries and circulating throughout the Islamic world in general. His light illuminates the lamps of science and knowledge for them, especially through his poems, which he grew up with from a young age, and his longing and love for the noble Messenger, may God bless him and grant him peace, prompted him to praise him with pearl necklaces that are unparalleled, and his mastery of the sciences, as he published more than fifty books in various modern sciences. He is none other than the brilliant Sheikh (Ma'ruf al-Nawdahi), who became more famous than a fire on a flag and is pointed to with fingers. And here, among his vast knowledge, we wanted our research to be about doctrine and (the revealed things in particular) and his position on them, because there are opinions that have confused people’s thoughts, so perhaps God will guide us and them to the right path, for He is the Guardian of that and is capable of it.